Dynamic Force Analysis of Single Acting Compressor Based on Angular Velocity - Hartono, Budi; Sutoyo, Edy; Sutisna, Satya Permana; Al-Kindi, Hablinur; Suhada, Rohman (Journal of Applied Science and Advanced Engineering, 2025)
This paper presents a dynamic force analysis of a single-action piston compressor operating at various crankshaft angular velocities. The analysis was performed using Scilab and CADCAM software tools to evaluate the inertia forces acting on the crankshaft, connecting rod, and piston head. At a crankshaft speed of 1500 rpm, the inertia force on the crankshaft was calculated as 0.03 N, increasing to 0.055 N at 2000 rpm and 0.066 N at 2200 rpm. For the connecting rod, the corresponding forces were 17.51 N, 31.12 N, and 37.66 N, respectively. At the piston head, the inertia force rose from 0.063 N at 1500 rpm to 0.11 N at 2000 rpm, and 0.14 N at 2200 rpm. The results indicate that variatioins in angular velocity significantly affect the magnitude of dynamic forces within the compressor components.